Aerosolization behavior of antimicrobial resistance in animal farms: a field study from feces to fine particulate matter - Xin, Huibo; Qiu, Tianlei; Guo, Yajie; Gao, Haoze; Zhang, Liqiu; Gao, Min (Frontiers in Microbiology, 2023)
Antibiotic resistance genes (ARGs) and antibiotic resistance bacteria (ARB) in animal feces could be released into the atmospheric environment via aerosolization, posing a high health risk to farm workers. So far, little attention has been paid to characterize their aerosolization process. In this study, we collected fecal and fine particulate matter (PM2.5) samples from 20 animal farms involving swine, cattle, layer and brolier, and analyzed the ARGs, ARB and human pathogenic bacteria (HPB) loaded in those two media. The results showed that approximately 70% of ARGs, 60% of ARBs, and 43% HPB were found to be preferential aerosolization. The bioaerosolization index (BI) of target 30 ARGs varied from 0.04 to 460.07, and the highest value was detected from tetW. The highest BI value of Erythromycin- and Tetracycline-resistant bacteria was Kocuria (13119), and Staphylococcus (24746), respectively, and the distribution of BI in two types of dominant ARB were similar. In terms of the bioaerosolization behavior of HPB, Clostridium saccharolyticum WM1 was the most easily aerosolized pathogens in swine and brolier farms, and Brucella abortus strain CNM 20040339 had the highest value at cattle and layer farms. Of note, the highest BI of ARGs, ARB, and HPB were universally detected from chicken farms. Most ARGs, ARB and HPB were positively correlated with the animal age, stocking density and breeding area. Temperature and relative humidity have significant effects on the aerosolization behavior of targets, and the effects of those two parameters on the same target were usually opposite. The results of this study provide a basis for better understanding the contribution of animal feces to airborne ARGs and HPBs in farms, as well as for controlling the transport of fecal microbiome to the environment through the aerosolization pathway.